Thermally conductive silicone composition
By using the composition of organopolysiloxane, hydrolyzable organopolysiloxane and thermally conductive powder filler in the thermal paste, the problem of deterioration of the thermal paste in a high temperature and high humidity environment is solved, and high thermal conductivity and stability are achieved , avoiding deterioration of thermal resistance value and void generation.
Patent Information
- Application Number
- CN202380023213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-28
- Filing Date
- 2023-02-03
- Publication Date
- 2024-12-13
AI Technical Summary
The existing thermal paste deteriorates in high temperature and high humidity environments, resulting in deterioration of thermal resistance and void generation, and cannot effectively follow and adhere to the concave and convex surface of the IC package, affecting thermal conductivity.
The thermally conductive silicone composition including organopolysiloxane, hydrolyzable organopolysiloxane, thermally conductive powder filler and platinum catalyst is used to increase the filler filler and the long chain by adding reaction curing composition. Alkyl organosilane ensures that high thermal conductivity and no voids are created at high temperatures and high humidity.
It achieves stable thermal resistance value in high temperature and high humidity environments, avoids high elastic modulus and void generation, maintains high thermal conductivity and good ductility and stability, and extends shelf life and applicable period.
Smart Images

Figure CN119137215A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive organic silicon composition (a thermally conductive addition-curable organic silicon composition). Background Art
[0002] Electronic components mounted on a printed circuit board, such as an IC package such as a CPU, may sometimes suffer performance degradation or damage due to temperature rise caused by heat dissipation during use. Therefore, a heat sink sheet or heat dissipation paste with good thermal conductivity has always been used between the IC package and the heat sink fins (Patent Document 1 to Patent Document 6).
[0003] In particular, thermal paste is not affected by the unevenness of the surface of components such as the CPU and heat sink fins, and can follow and adhere to their attached surfaces, so it can exert higher performance. In recent years, high heat dissipation performance has become a must, so there is a tendency to use thermal paste filled with a large amount of thermal conductive fillers, but if it is exposed to high temperature and high humidity in order to fill a large amount of fillers, the following problems will arise: the thermal paste will continue to deteriorate, resulting in insufficient following and adhesion to the covered surface, causing the thermal resistance value to deteriorate or voids to appear.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-003718
[0007] Patent Document 2: Japanese Patent Application Publication No. 2002-327116
[0008] Patent Document 3: Japanese Patent Application Publication No. 2008-031336
[0009] Patent Document 4: Japanese Patent Application Publication No. 2013-091726
[0010] Patent Document 5: Japanese Patent Application Publication No. 2015-078296
[0011] Patent Document 6: Japanese Patent Application Publication No. 2015-183184 Summary of the invention
[0012] 1. Technical issues to be resolved
[0013] The present invention improves the above situation, and an object of the present invention is to provide a thermally conductive silicone composition whose thermal resistance value does not deteriorate even when exposed to high temperature and high humidity, whose elastic modulus does not increase even when exposed to high temperature, whose voids do not occur, and whose thermal conductivity is high.
[0014] (II) Technical solution
[0015] In order to solve the above technical problems, the present invention provides a thermally conductive silicone composition, which comprises:
[0016] (A) 100 parts by mass of an organopolysiloxane having at least two alkenyl groups in one molecule;
[0017] (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule, wherein the organohydrogenpolysiloxane is in such an amount that the ratio of the number of Si-H groups in the component (B) to the number of alkenyl groups in the component (A) (the number of Si-H groups) / (the number of alkenyl groups) is 0.5 to 3.0;
[0018] (C) a filler comprising one or more thermally conductive powders, which is 800 to 20,000 parts by mass;
[0019] (D) 20 to 400 parts by mass of a hydrolyzable organopolysiloxane represented by the following general formula (1),
[0020] [Chemical formula 1]
[0021]
[0022] R in the general formula (1) 1 represents a monovalent hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, and each R 1 are optionally the same or different, and a is 5 to 100;
[0023] (E) 0.01 to 100 parts by mass of an organosilane represented by the following general formula (2),
[0024] R 2 b Si(OR 3 ) 4-b (2)
[0025] In the general formula (2), R 2 is one or more groups selected from a saturated or unsaturated monovalent hydrocarbon group having 14 to 20 carbon atoms, an epoxy group, and a (meth)acryloyl group, and R 3 is an alkyl group having 1 to 6 carbon atoms, and b is an integer of 1 to 3;
[0026] (F) a catalyst of platinum or a platinum compound, in an amount of 0.1 to 500 ppm based on the component (A) in terms of platinum atoms; and
[0027] (G) A reaction control agent, which is 0.01 to 1 part by mass.
[0028] Such a thermally conductive silicone composition can provide a thermally conductive silicone composition having a high thermal conductivity without deteriorating thermal resistance even when exposed to high temperature and high humidity, without increasing elastic modulus or generating voids even when exposed to high temperature.
[0029] In addition, it is preferred that the viscosity of the component (A) is 10 to 100,000 mm2 at 25°C. 2 / s.
[0030] Such a thermally conductive silicone composition has good storage stability and good ductility.
[0031] Furthermore, it is preferred that the component (C) contains aluminum powder and zinc oxide powder.
[0032] Such a thermally conductive silicone composition has excellent stability and does not cause oil separation.
[0033] In addition, it is preferred that the R of the component (E) 2 It is an alkyl group having 14 to 20 carbon atoms.
[0034] Such a thermally conductive silicone composition is less likely to volatilize and does not generate voids even at high temperatures, is easy to handle, and does not deteriorate in low-temperature properties.
[0035] In addition, it is preferred that the R of the component (E) 2 It is an alkyl group having 16 to 20 carbon atoms.
[0036] Such a thermally conductive silicone composition is less likely to volatilize, does not generate voids even at high temperatures, is easy to handle, and does not deteriorate in low-temperature properties.
[0037] Furthermore, it is preferred that the component (G) contains at least one of an acetylene compound, a nitrogen compound, an organic phosphorus compound, an oxime compound, and an organic chlorine compound.
[0038] Such a thermally conductive silicone composition can suppress the progress of the hydrosilylation reaction at room temperature, thereby extending the shelf life and pot life.
[0039] In addition, it is preferred that the viscosity of the thermally conductive silicone composition at 25° C. is in the range of 50 to 1,000 Pa·s.
[0040] Such a thermally conductive silicone composition does not become uneven due to precipitation of the thermally conductive filler during storage, and has ductility without reducing the working efficiency.
[0041] Furthermore, it is preferred that even after a highly accelerated stress test (130° C., 85% humidity, 96 hours), the thermal resistance of the cured product of the thermally conductive silicone composition is not more than 1.5 mm higher than that before the highly accelerated stress test. 2 ·K / W or above.
[0042] Such a thermally conductive silicone composition can maintain the thermal resistance performance for a long period of time.
[0043] Furthermore, for the thermally conductive silicone composition, preferably, after the cured product is sandwiched between two glass plates and cured at 150° C. for 60 minutes, no voids are observed even after heating at 260° C. for 5 minutes is repeated five times.
[0044] Such a thermally conductive silicone composition can suppress the occurrence of voids even at high temperatures.
[0045] Furthermore, it is preferred that the cured product of the thermally conductive silicone composition has a hardness of 10 or more as measured by Asker C at 25°C.
[0046] According to such a thermally conductive silicone composition, the cured product after heating does not become brittle and does not break.
[0047] Furthermore, it is preferred that the cured product of the thermally conductive silicone composition does not have a tensile modulus that is increased by more than 20 MPa compared to before the heating test even after a heating test in which the cured product is placed in a chamber at 260° C. for 5 minutes and then taken out three times.
[0048] Such a thermally conductive silicone composition can suppress an increase in tensile modulus even when exposed to high temperatures.
[0049] (III) Beneficial effects
[0050] As described above, the thermally conductive silicone composition of the present invention can provide a thermally conductive silicone composition having a high thermal conductivity and having no deterioration in thermal resistance even when exposed to high temperature and high humidity, no high elastic modulus even when exposed to high temperature, and no voids. DETAILED DESCRIPTION
[0051] As described above, a thermally conductive silicone composition and a cured product thereof are sought to be developed, wherein the thermal resistance value does not increase and deteriorate even when exposed to high temperature and high humidity, the elastic modulus does not increase even when exposed to high temperature, and voids do not occur, and the thermal conductivity is high.
[0052] The inventors of the present application have conducted in-depth studies on the above technical problems and have found that, in order to achieve the above purpose, by blending a filler containing one or more thermally conductive powders and an organosilane having a long-chain alkyl group represented by the general formula (2) into an addition reaction-curable silicone composition, the filling amount of the filler can be increased. As a result, a thermally conductive silicone composition can be obtained, which can obtain a sufficient thermal conductivity, and the thermal resistance value will not deteriorate even when exposed to high temperature and high humidity, and will not generate voids even when exposed to high temperature. The present invention has been completed. The addition reaction-curable silicone composition comprises: (A) an organopolysiloxane having at least two alkenyl groups in one molecule, and (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule.
[0053] That is, the present invention is a thermally conductive silicone composition comprising:
[0054] (A) 100 parts by mass of an organopolysiloxane having at least two alkenyl groups in one molecule;
[0055] (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule, wherein the organohydrogenpolysiloxane is in such an amount that the ratio of the number of Si-H groups in the component (B) to the number of alkenyl groups in the component (A) (the number of Si-H groups) / (the number of alkenyl groups) is 0.5 to 3.0;
[0056] (C) a filler comprising one or more thermally conductive powders, which is 800 to 20,000 parts by mass;
[0057] (D) 20 to 400 parts by mass of a hydrolyzable organopolysiloxane represented by the following general formula (1),
[0058] [Chemical formula 2]
[0059]
[0060] R in the general formula (1) 1 represents a monovalent hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, and each R 1 are optionally the same or different, and a is 5 to 100;
[0061] (E) 0.01 to 100 parts by mass of an organosilane represented by the following general formula (2),
[0062] R 2 b Si(OR 3 ) 4-b (2)
[0063] In the general formula (2), R 2is one or more groups selected from a saturated or unsaturated monovalent hydrocarbon group having 14 to 20 carbon atoms, an epoxy group, and a (meth)acryloyl group, and R 3 is an alkyl group having 1 to 6 carbon atoms, and b is an integer of 1 to 3;
[0064] (F) a catalyst of platinum or a platinum compound, in an amount of 0.1 to 500 ppm based on the component (A) in terms of platinum atoms; and
[0065] (G) A reaction control agent, which is 0.01 to 1 part by mass.
[0066] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.
[0067] [Thermal conductive silicone composition]
[0068] ((A) ingredient)
[0069] The organopolysiloxane constituting the component (A) of the thermally conductive silicone composition of the present invention has at least two alkenyl groups directly bonded to silicon atoms in one molecule and may be linear or branched, or may be a mixture of two or more types having different viscosities.
[0070] Examples of alkenyl groups include vinyl, allyl, propenyl, isopropenyl, 1-butenyl, 1-hexenyl, cyclohexenyl, octenyl, etc. Examples include groups in which some or all of the hydrogen atoms of these groups are replaced by halogen atoms such as fluorine, bromine, and chlorine, cyano, etc., such as chloromethyl, chloropropyl, bromoethyl, 3,3,3-trifluoropropyl, cyanoethyl, etc. In terms of ease of synthesis and cost, vinyl is particularly preferred.
[0071] Examples of the remaining functional groups bonded to the silicon atom include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, decyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenethyl, and 2-phenylpropyl. Among them, methyl is particularly preferred from the perspective of ease of synthesis and cost.
[0072] At this time, at least 2 of them must be alkenyl groups (particularly preferably alkenyl groups having 2 to 8 carbon atoms, and more preferably alkenyl groups having 2 to 6 carbon atoms). The upper limit of the number of alkenyl groups is not particularly limited, and can be determined according to the molecular composition of the organopolysiloxane of component (A), and is typically 9. The alkenyl group may be bonded to a silicon atom at the end of the molecular chain, to a silicon atom in the molecular chain, or to a silicon atom at the end of the molecular chain and to a silicon atom in the molecular chain. However, from the perspective of the curing speed of the composition, the physical properties of the cured product, etc., the organopolysiloxane used in the present invention preferably contains at least an alkenyl group bonded to a silicon atom at the end of the molecular chain.
[0073] The viscosity of the organopolysiloxane of the component (A) at 25°C is not particularly limited. 2 / s or more, the storage stability of the composition is good, and if it is 100,000mm 2 / s or less, the ductility of the obtained composition is good, so it is preferably 10 to 100,000 mm 2 / s, more preferably 100~80,000mm 2 / s range.
[0074] In the present invention, the dynamic viscosity is a value measured at 25° C. using an Ubbelohde-type Ostwald viscometer (the same shall apply hereinafter).
[0075] ((B) ingredient)
[0076] The component (B) is an organohydrogenpolysiloxane represented by the following average composition formula (3) and having at least two hydrogen atoms bonded to silicon atoms in one molecule. The organohydrogenpolysiloxane preferably has 3 to 100 hydrogen atoms bonded to silicon atoms in one molecule, more preferably 3 to 50, and even more preferably 3 to 20.
[0077] R 4 c H d SiO (4-c-d) / 2 (3)
[0078] In the average composition formula (3), R 4 is an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, and further, c is 0.7 to 2.2, d is 0.001 to 0.5, and c+d is a positive number satisfying 0.8 to 2.5.
[0079] In the above formula (3), R 4It is independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, and the number of carbon atoms is not particularly limited, but is preferably usually 1 to 10, and more preferably 1 to 6. Specific examples thereof include: alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, phenethyl, and phenylpropyl; and 3,3,3-trifluoropropyl groups in which some or all of the hydrogen atoms of these groups are replaced by halogen atoms such as chlorine, bromine, and fluorine. Among them, alkyl groups, aryl groups, and 3,3,3-trifluoropropyl groups are preferred, and methyl groups, phenyl groups, and 3,3,3-trifluoropropyl groups are more preferred.
[0080] In addition, c is preferably a positive number of 0.7 to 2.2, and more preferably a positive number of 1.0 to 2.1. d is preferably a positive number of 0.001 to 0.5, and more preferably a positive number of 0.005 to 0.1. c+d is preferably in the range of 0.8 to 2.5, and more preferably in the range of 1.0 to 2.5, and even more preferably in the range of 1.5 to 2.2.
[0081] The number of silicon atoms in one molecule of the organohydrogenpolysiloxane of the component (B) (i.e., degree of polymerization) is not particularly limited, but is usually preferably 10 to 1,000, more preferably 20 to 500, and even more preferably 20 to 100, from the viewpoint of improving the handling workability of the composition and the properties of the obtained cured product.
[0082] The molecular structure of the organohydrogenpolysiloxane of the component (B) is not particularly limited as long as it satisfies the above requirements. The viscosity of the organohydrogenpolysiloxane of the component (B) is also not particularly limited, but is generally preferably 1 to 10,000 mPa·s, more preferably 3 to 2,000 mPa·s, and even more preferably 10 to 1,000 mPa·s. It is desirable that the organohydrogenpolysiloxane is liquid at room temperature (25° C.).
[0083] Examples of the organohydrogenpolysiloxane represented by the formula (3) include methylhydrogensiloxane-dimethylsiloxane cyclic copolymers, methylhydrogenpolysiloxane terminated by dimethylhydrogensiloxy groups at both ends, methylhydrogen-dimethylsiloxane copolymer terminated by dimethylhydrogensiloxy groups at both ends, methylhydrogen-diphenylsiloxane copolymer terminated by dimethylhydrogensiloxy groups at both ends, methylhydrogen-dimethylsiloxane-diphenylsiloxane copolymer terminated by dimethylhydrogensiloxane groups at both ends, methylhydrogenpolysiloxane terminated by trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer terminated by trimethylsiloxy groups at both ends, methylhydrogen-diphenylsiloxane-dimethylsiloxane copolymer terminated by trimethylsiloxy groups at both ends; and methylhydrogenpolysiloxane terminated by (CH 3 )2 HSiO 1 / 2 Unit, (CH 3 ) 2 HSiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, (C 6 H 5 ) 2 SiO unit, (CH 3 ) 2 SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 )(C 6 H 5 )HSiO 1 / 2 Unit, (CH 3 ) 2 SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, (CH 3 ) 2 SiO unit and C 6 H 5 SiO 3 / 2 A copolymer composed of (CH 3 )(CF 3 C 2 H 4 )HSiO 1 / 2 Unit, (CH 3 )(CF 3 C 2 H 4 )SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 )(CF 3 C 2 H 4 )HSiO 1 / 2 Unit, (CH 3 )(CF 3 C 2 H 4 )SiO unit, (CH 3 ) 2 SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3) 2 HSiO 1 / 2 Unit, (CH 3 )(CF 3 C 2 H 4 )SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, (CH 3 )(CF 3 C 2 H 4 )SiO unit, (CH 3 ) 2 SiO unit and CH 3 SiO 3 / 2 A copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, (CH 3 )(CF 3 C 2 H 4 )SiO unit, (CH 3 ) 2 SiO unit and (CF 3 C 2 H 4 )SiO 3 / 2 Copolymers composed of units, etc.
[0084] The organohydrogenpolysiloxane of the component (B) may be used alone or in combination of two or more. The organohydrogenpolysiloxane can be synthesized by a conventionally known method.
[0085] If the blending amount of the component (B) is such that the ratio of the number of Si-H groups in the component (B) to the number of alkenyl groups in the component (A), i.e., {the number of Si-H groups} / {the number of alkenyl groups}, is less than 0.5, a sufficient network structure cannot be obtained, and the necessary hardness cannot be obtained after curing, so voids may be generated. If it is greater than 3.0, unreacted Si-H groups may cause excessive crosslinking reaction due to moisture or the like, resulting in hardening, loss of flexibility of the composition, and significant deterioration of thermal resistance after a highly accelerated stress test. Therefore, it is necessary to be in the range of 0.5 to 3.0, preferably in the range of 0.6 to 2.0.
[0086] ((C) ingredient)
[0087] The filler of the component (C) of the present invention is used to impart thermal conductivity to the composition of the present invention, and includes one or more thermally conductive powders. If the thermal conductivity of the component (C) is 10 W / m·°C or more, the thermal conductivity of the composition can be sufficiently ensured, and therefore, it is preferred to include a thermally conductive powder having a thermal conductivity of 10 W / m·°C or more.
[0088] As the powder type of the filler used for the component (C) of the present invention, aluminum powder and zinc oxide powder are preferably used. If the average particle size of the aluminum powder is 0.1 μm or more, the viscosity of the obtained composition will not become too high, and the ductility can be ensured. If it is 100 μm or less, the obtained composition will not become non-uniform. Therefore, although not particularly limited, it is preferably in the range of 0.1 to 100 μm, and more preferably in the range of 1 to 50 μm.
[0089] In addition, if the average particle size of the zinc oxide powder is 0.1 μm or more, the viscosity of the obtained composition will not become too high, and the ductility can be ensured. If it is 5 μm or less, the obtained composition will not become non-uniform. Therefore, although it is not particularly limited, it is preferably in the range of 0.1 to 5 μm, and more preferably in the range of 1 to 4 μm. In addition, the shape of the aluminum powder and the zinc oxide powder can be any of spherical and irregular shapes.
[0090] The thermal conductivity of the aluminum powder and zinc oxide powder as the above-mentioned thermally conductive powder is about 237W / m·K and about 20W / m·K, respectively, so a high thermal conductivity can be obtained, so it is preferred to use the above-mentioned mineral in the filler. As the filler of the (C) component of the present invention, aluminum powder can be used alone, but by mixing with zinc oxide powder, oil separation can be suppressed, and the stability of the obtained composition can be maintained. Its ratio is not particularly limited, and in terms of weight ratio, preferably aluminum powder: zinc oxide powder is in the range of 1:1 to 10:1, and more preferably in the range of 2:1 to 8:1. If the ratio of aluminum powder is 1:1 or more, the thermal conductivity of the obtained composition will not decrease, and if it is 10:1 or less, the oil separation over time can be further suppressed.
[0091] The amount of the filler is 800 to 20,000 parts by mass, preferably 850 to 7,000 parts by mass, per 100 parts by mass of the component (A). If it is less than 800 parts by mass, the thermal conductivity of the obtained composition will be poor, and if it is more than 20,000 parts by mass, it will be difficult to prepare a paste.
[0092] ((D) ingredient)
[0093] The component (D) of the present invention is a hydrolyzable organopolysiloxane represented by the following general formula (1).
[0094] [Chemical formula 3]
[0095]
[0096] R in the general formula (1) 1 represents a monovalent hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, and each R 1 can be the same or different. and a is 5 to 100.
[0097] The component (D) is used as a wetting agent. The wettability of the component (A) and the filler is poor. If the wetting agent is not added and mixed, a sufficient filling amount cannot be obtained. Based on this point, a study was conducted and it was found that the filling amount of the filler can be significantly increased by adding the organopolysiloxane of the general formula (1). In the general formula (1), R 1 It is an alkyl group having 1 to 10 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms. Specifically, it includes methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, tert-butyl, pentyl, hexyl and the like.
[0098] The a of composition formula (1) is 5 to 100, preferably 10 to 60. If a is less than 5, the oil bleeding of the composition may become serious and may produce gaps. If a is greater than 100, the viscosity of the composition may become high and workability may deteriorate. The addition amount is 20 to 400 parts by mass relative to the total amount of the composition, preferably 40 to 200 parts by mass. If the addition amount is less than 20 parts by mass relative to the total amount, the wettability of the composition may become insufficient, and if the addition amount is more than 400 parts by mass relative to the total amount, the oil bleeding of the composition may become serious and may produce gaps.
[0099] ((E) ingredient)
[0100] The component (E) of the present invention is an organosilane represented by the following general formula (2).
[0101] R 2 b Si(OR 3 ) 4-b (2)
[0102] In the general formula (2), R 2 is one or more groups selected from a saturated or unsaturated monovalent hydrocarbon group having 14 to 20 carbon atoms, an epoxy group, and a (meth)acryloyl group, and R 3 is an alkyl group having 1 to 6 carbon atoms. b is an integer of 1 to 3.
[0103] It was found that the component (E) has the effect of being a wetting agent that significantly increases the filling amount of the filler, similarly to the component (D), and also has the effect of significantly suppressing the deterioration of the thermal resistance value even when exposed to high temperature and high humidity.
[0104] Here, in the above formula (2), R 2 It is one or more groups selected from a saturated or unsaturated monovalent hydrocarbon group, an epoxy group, and a (meth)acryloyl group, which may have a carbon number of 14 to 20, and preferably an alkyl group having a carbon number of 14 to 20, more preferably an alkyl group having a carbon number of 16 to 20, and more preferably an alkyl group having a carbon number of 16 to 18. For example, hexadecyl and octadecyl groups are listed. If the number of carbon atoms is less than 14, it is easy to volatilize and may produce voids at high temperatures. If it is more than 20, the organosilane will solidify at room temperature, which is inconvenient to handle, and the low-temperature properties of the resulting composition will be reduced. In addition, b is an integer of 1 to 3, and is particularly preferably 1. R in the above general formula (2) 3 It is an alkyl group having 1 to 6 carbon atoms, and methyl and ethyl groups are particularly preferred.
[0105] Specific examples of the organosilane of the component (E) represented by the general formula (2) include the following components.
[0106] C 14 H 29 Si(OCH 3 ) 3
[0107] C 16 H 33 Si(OCH 3 ) 3
[0108] C 18 H 37 Si(OCH 3 ) 3
[0109] C 20 H 41 Si(OCH 3 ) 3
[0110] C 16 H 33 Si(OC 2 H 5 ) 3
[0111] C 18 H 37 Si(OC 2 H 5 ) 3
[0112] If the blending amount of the organosilane as the above-mentioned (E) component is less than 0.01 parts by mass relative to 100 parts by mass of the (A) component, the wettability is poor and the flexibility cannot be maintained under high temperature and high humidity for a long time. Even if the blending amount exceeds 100 parts by mass, the effect will not increase, and the economic efficiency is poor. Voids will be generated at high temperatures. Therefore, the range is 0.01 to 100 parts by mass, preferably 10 to 70 parts by mass.
[0113] ((F) ingredient)
[0114] The catalyst selected from platinum and platinum compounds of the (F) component is a component that promotes the addition reaction between the alkenyl group of the (A) component and the Si-H group of the (B) component. The (F) component, for example, can include a simple platinum substance, chloroplatinic acid, a platinum-olefin complex, a platinum-alcohol complex, a platinum coordination compound, etc. Relative to 100 parts by mass of the (A) component, if the admixture of the (F) component is less than 0.1ppm in terms of platinum atoms, it does not have the effect of being a catalyst, and even if it is admixed with more than 500ppm, it is also impossible to particularly expect the improvement of the curing speed, so it is in the range of 0.1 to 500ppm, more preferably in the range of 1 to 200ppm.
[0115] ((G) ingredient)
[0116] The reaction control agent of the component (G) inhibits the progress of the hydrosilylation reaction at room temperature, thereby extending the shelf life and the applicable period. As the reaction control agent of the component (G), a known reaction control agent can be used, and acetylene compounds, various nitrogen compounds, organic phosphorus compounds, oxime compounds, organic chlorine compounds, etc. can be utilized. If the blending amount of the component (G) is less than 0.01 parts by mass relative to 100 parts by mass of the component (A), sufficient shelf life and applicable period cannot be obtained, and if it is more than 1 part by mass, the curability will be reduced, so it is in the range of 0.01 to 1 parts by mass, preferably in the range of 0.1 to 0.8 parts by mass.
[0117] In addition to the above-mentioned components (A) to (G), the thermally conductive silicone composition of the present invention may also contain an adhesive additive or the like to chemically bond and fix an IC package such as a CPU to a heat dissipating body such as a heat sink, and may also contain an antioxidant or the like to prevent degradation.
[0118] The thermally conductive silicone composition of the present invention can be prepared into a one-liquid addition type by mixing the above-mentioned components (A) to (G) and other optional components, and can be stored at low temperatures for a long period of time.
[0119] [Method for preparing thermally conductive silicone composition]
[0120] The thermally conductive silicone composition of the present invention can be prepared by mixing the above components. The order of adding the components is not particularly limited, and the composition can be prepared by mixing the components (A) to (G) and any other components as required. For example, a portion containing the components (A), (C) and (D) and a portion containing the component (B) can be prepared separately, and then the two portions can be mixed for use.
[0121] The components of the silicone composition of the present invention may be mixed at room temperature or heated, and the mixing temperature is preferably 25 to 200° C., more preferably 50 to 180° C. The mixture may be further heated or degassed during mixing at 25° C.
[0122] [Physical properties of thermally conductive silicone composition]
[0123] The viscosity of the silicone composition of the present invention is preferably 50 to 1000 Pa·S, more preferably 100 to 700 Pa·S, and even more preferably 150 to 400 Pa·S when measured at 25°C using a Malcom rotational viscometer (rotation speed 10 rpm). If it is 50 Pa·S or more, the thermal conductive filler will not precipitate or become uneven during storage, and if it is 1000 Pa·S or less, ductility can be ensured and work efficiency will not be reduced.
[0124] Even after the highly accelerated stress test (130°C, 85% humidity, 96 hours), the thermal resistance of the cured product of the silicone composition of the present invention does not increase and deteriorate by 1.5 mm compared to before the highly accelerated stress test. 2 ·K / W or more, so the thermal resistance performance can be sustained for a long time. In addition, the lower the thermal resistance value, the better the thermal performance, so no matter how much it decreases after the test compared to before the test, it will not cause any problem.
[0125] The silicone composition of the present invention can suppress the generation of voids even at high temperatures. After the composition was sandwiched between two glass plates and cured at 150° C. for 60 minutes, no voids were observed even after heating at 260° C. for 5 minutes was repeated five times.
[0126] The cured product of the silicone composition of the present invention can suppress the high tensile modulus even when exposed to high temperature, and even if a heating test is performed, the tensile modulus will not increase by more than 20 MPa compared with before the heating test. The heating test is repeated 3 times in a process of placing in a chamber at 260°C for 5 minutes and then taking it out. In addition, the less the tensile modulus changes compared with before the heating test, the more constant the thermal performance can be maintained, so no matter how small the change is, it will not cause any problem.
[0127] The hardness of the cured product of the silicone composition of the present invention is preferably 10 or more, more preferably 20 to 90, and even more preferably 30 to 85, when measured by Asker C at 25°C. When the hardness is 10 or more, the cured product after the heating test will not become brittle and will not be damaged.
[0128] Example
[0129] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited thereto.
[0130] First, prepare the following ingredients.
[0131] (A)Ingredients
[0132] A-1: Both ends are capped with dimethylvinylsilyl groups and the viscosity at 25°C is 600 mm 2 / s dimethyl polysiloxane
[0133] A-2: Both ends are capped with dimethylvinylsilyl groups and the viscosity at 25°C is 30,000 mm 2 / s dimethyl polysiloxane
[0134] A-3: Both ends are capped with trivinylsilyl groups and the viscosity at 25°C is 1,500 mm 2 / s dimethyl polysiloxane
[0135] (B) Ingredients
[0136] B-1: has 2 hydrogen atoms bonded to silicon atoms on the side chain and a viscosity of 30 mm 2 / s organohydrogenpolysiloxane
[0137] B-2: Both ends have hydrogen atoms bonded to silicon atoms, the side chain has 2 hydrogen atoms bonded to silicon atoms, and the viscosity is 40 mm 2 / s organohydrogenpolysiloxane
[0138] (C) Ingredients
[0139] C-1: Aluminum powder with an average particle size of 10 μm
[0140] C-2: Zinc oxide powder with an average particle size of 0.25 μm
[0141] (D) Ingredients
[0142] D-1: Organohydrogenpolysiloxane represented by the following formula
[0143] [Chemical formula 4]
[0144]
[0145] (E) Ingredients
[0146] E-1: C 10 H 21 Si(OCH 3 ) 3 (for comparative example)
[0147] E-2: C 12 H 25 Si(OCH 3 ) 3 (for comparative example)
[0148] E-3:C 16 H 33 Si(OCH 3 ) 3
[0149] E-4: C 18 H 37 Si(OCH 3 ) 3
[0150] (F)Ingredients
[0151] F-1: Platinum-divinyltetramethyldisiloxane complex having a platinum concentration of 1 mass %
[0152] (G) Ingredients
[0153] G-1: 1-ethynyl-1-cyclohexanol
[0154] The above components (A) to (G) were mixed in the following manner to obtain thermally conductive silicone compositions of Examples 1 to 7 and Comparative Examples 1 to 8. Specifically, components (A), (C), (D), and (E) were added to a 5-liter planetary mixer (manufactured by INOUE MFG., INC.) and mixed at 170° C. for 90 minutes. After cooling to room temperature, components (B), (F), and (G) were added and mixed one by one for 15 minutes.
[0155] The properties of the obtained compositions were evaluated by the following methods. The results are shown in Tables 1 and 2.
[0156] (1) Viscosity: The viscosity at 25°C was measured using a Macon rotational viscometer (rotation speed 10 rpm).
[0157] (2) Thermal conductivity: The thermal conductivity of the composition before curing at 25° C. was measured using a thermal property measuring apparatus TPS-2500S manufactured by KYOTO ELECTRONICS MANUFACTURING CO., LTD.
[0158] (3) Thermal resistance: The composition was clamped between a 15 mm × 15 mm × 1 mmt Si chip and a 15 mm × 15 mm × 1 mmt Ni plate, and the composition was cured at 150°C for 60 minutes to prepare a test piece for thermal resistance measurement, and the thermal resistance value was measured. Furthermore, thereafter, the test piece was placed in a chamber at 130°C and 85% humidity for 96 hours, and a highly accelerated stress test was performed. The thermal resistance value was measured after the highly accelerated stress test, and the thermal resistance values before and after the highly accelerated stress test were compared. In addition, the thermal resistance measurement was performed using a laser flash thermal conductivity meter (NanoFlash) (manufactured by NETZSCH, LFA447).
[0159] (4) Gap test: The composition was sandwiched between two glass plates, and both ends were clamped with clips, and the composition was cured at 150°C for 60 minutes. Furthermore, heating at 260°C for 5 minutes was repeated 5 times, and the state of the composition sandwiched between the glass plates was visually confirmed.
[0160] No voids in the composition: ○
[0161] There are gaps in the composition: ×
[0162] (5) Tensile modulus: The silicone composition was cured at 150°C for 60 minutes to form a 2 mm thick sheet, and the tensile modulus at 25°C was measured using ARES-G2 manufactured by TA Instruments. The cured product of the silicone composition was then placed in a high temperature chamber at 260°C (STH-120, a small high temperature test chamber manufactured by ESPEC Corp.) for 5 minutes, and then a heating test was performed in which the steps of taking the cured product out of the high temperature chamber and returning it to room temperature were repeated three times, and the tensile modulus at 25°C was measured using the same apparatus as described above.
[0163] (6) Hardness: After the silicone composition was cured at 150° C. for 60 minutes, the hardness at 25° C. was measured using Asker C.
[0164] [Table 1]
[0165]
[0166] [Table 2]
[0167]
[0168] ※ The number of moles of the component (E) in Example 3, Example 5, Example 6, Example 7, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 6, and Comparative Example 7 are equal.
[0169] ※2 Cannot be made into a paste.
[0170] ※3 The cured product became brittle due to the formation of voids and was broken during the measurement of tensile modulus, so it could not be measured.
[0171] Based on the results of Table 1 and Table 2, the thermally conductive silicone compositions of Examples 1 to 7 that satisfy the requirements of the present invention can achieve a composition that is not only thermally conductive but also maintains a low viscosity, has little degradation in thermal resistance even after a highly accelerated stress test, and has little generation of voids and increase in elastic modulus even after a heating test.
[0172] On the other hand, since the organosilane having a long-chain alkyl group was not blended in Comparative Example 1, the thermal resistance value increased significantly after the highly accelerated stress test.
[0173] Since C was added in Comparative Example 2 10 H 21 Si(OCH 3 ) 3 , which is an organosilane with a short alkyl chain length, the thermal resistance value after the highly accelerated stress test deteriorated significantly, and voids were also generated in the void test.
[0174] Since C was added in Comparative Example 3 12 H 25 Si(OCH 3 ) 3 The length of the alkyl chain is insufficient, so although the thermal resistance value after the highly accelerated stress test has not deteriorated substantially, the hardness is low and voids are generated after the void test.
[0175] Comparative Example 4 added the same C as in Comparative Example 3. 12 H 25 Si(OCH 3 ) 3 , the ratio of {the number of Si-H groups in component (B)} / {the number of Si-Vi groups in component (A)} was increased, but the tensile modulus after heating still increased significantly.
[0176] In Comparative Example 5, the same amount of C as in Comparative Examples 3 and 4 was reduced. 12 H 25 Si(OCH 3 ) 3 Due to the addition amount, the thermal resistance value after the highly accelerated stress test deteriorates and the tensile modulus after heating also increases significantly.
[0177] Since a large amount of filler was blended in Comparative Example 6, the viscosity increased significantly and the product could not be made into a paste but was in a lumpy state.
[0178] In Comparative Example 7, since the ratio of {the number of Si-H groups in component (B)} / {the number of Si-Vi groups in component (A)} is less than 0.5 and is too low, the strength of the material cannot be fully obtained, and voids are generated after the void test, or the cured product is brittle when heated, and the tensile modulus cannot be measured.
[0179] In Comparative Example 8, since a large amount of organosilane having a long-chain alkyl group was blended, voids were generated after the void test, or the cured product was brittle and the tensile modulus could not be measured.
[0180] The results of the above examples show that the thermally conductive silicone composition of the present invention can provide a thermally conductive silicone composition that does not deteriorate in thermal resistance even when exposed to high temperature and high humidity, does not increase in elastic modulus even when exposed to high temperature, does not generate voids, and has high thermal conductivity.
[0181] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and all technical solutions having substantially the same configuration and exerting the same functions and effects as the technical concept described in the claims of the present invention are included in the technical scope of the present invention.
Claims
1. A thermally conductive silicone composition, characterized in that: It contains: (A) 100 parts by mass of an organopolysiloxane having at least two alkenyl groups in one molecule; (B) an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule, wherein the organohydrogenpolysiloxane is in such an amount that the ratio of the number of Si-H groups in the component (B) to the number of alkenyl groups in the component (A) (the number of Si-H groups) / (the number of alkenyl groups) is 0.5 to 3.0; (C) a filler comprising one or more thermally conductive powders, which is 800 to 20,000 parts by mass; (D) 20 to 400 parts by mass of a hydrolyzable organopolysiloxane represented by the following general formula (1), [Chemical formula 1] R in the general formula (1) 1 represents a monovalent hydrocarbon group having 1 to 10 carbon atoms which may have a substituent, and each R 1 Optional the same or different, and a is 5 to 100; (E) 0.01 to 100 parts by mass of an organosilane represented by the following general formula (2), R 2 b Si(OR 3 ) 4-b (2) In the general formula (2), R 2 is one or more groups selected from a saturated or unsaturated monovalent hydrocarbon group having 14 to 20 carbon atoms, an epoxy group, and a (meth)acryloyl group, and R 3 is an alkyl group having 1 to 6 carbon atoms, and b is an integer of 1 to 3; (F) a catalyst of platinum or a platinum compound, in an amount of 0.1 to 500 ppm based on the component (A) in terms of platinum atoms; and (G) A reaction control agent, which is 0.01 to 1 part by mass.
2. The thermally conductive silicone composition according to claim 1, characterized in that: The viscosity of the component (A) is 10-100,000 mm at 25°C. 2 / s.
3. The thermally conductive silicone composition according to claim 1 or 2, characterized in that: The component (C) includes aluminum powder and zinc oxide powder.
4. The thermally conductive silicone composition according to any one of claims 1 to 3, characterized in that: The R of the component (E) 2 It is an alkyl group having 14 to 20 carbon atoms.
5. The thermally conductive silicone composition according to any one of claims 1 to 4, characterized in that: The R of the component (E) 2 It is an alkyl group having 16 to 20 carbon atoms.
6. The thermally conductive silicone composition according to any one of claims 1 to 5, characterized in that: The component (G) includes at least one of an acetylene compound, a nitrogen compound, an organic phosphorus compound, an oxime compound, and an organic chlorine compound.
7. The thermally conductive silicone composition according to any one of claims 1 to 6, characterized in that: The viscosity of the thermally conductive silicone composition at 25° C. is in the range of 50 to 1,000 Pa·s.
8. The thermally conductive silicone composition according to any one of claims 1 to 7, characterized in that: Even after the highly accelerated stress test (130°C, 85% humidity, 96 hours), the thermal resistance value of the cured product of the thermally conductive silicone composition is no higher than that before the highly accelerated stress test by 1.5 mm 2 ·K / W or above.
9. The thermally conductive silicone composition according to any one of claims 1 to 8, characterized in that: The cured product obtained by sandwiching the thermally conductive silicone composition between two glass plates and curing at 150° C. for 60 minutes was heated at 260° C. for 5 minutes five times, and no voids were observed.
10. The thermally conductive silicone composition according to any one of claims 1 to 9, characterized in that: The cured product of the thermally conductive silicone composition has a hardness of 10 or more as measured by Asker C at 25°C.
11. The thermally conductive silicone composition according to any one of claims 1 to 10, characterized in that: Even when the cured product of the thermally conductive silicone composition was subjected to a heating test, the tensile modulus did not increase by more than 20 MPa compared with that before the heating test. The heating test was repeated three times in a process of placing in a chamber at 260° C. for 5 minutes and then taking out.
